Robotic simulation with 2.0 tools to develop key competencies in Secondary Education. A case study - Esteban Vázquez Cano (Education in the knowledge society, 2012)
<span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: EN-US;" lang="EN-US">The paper presents a contextualized research in a secondary school in the province of Toledo in which he examines the design of a robotic simulation activity for the development of key competencies from an interdisciplinary and transversely way between the subjects of Technology, Spanish Language, English and Plastic and Visual Education. The design of the activity consisted on the development of an interdisciplinary project for the construction of a worm robot with an electronic device for measuring lengths. 2.0 free tools were used for designing it and   supported the development of four key competencies: Google Sketchup, Prezi, Glosgter and Windows Movie Maker . We analyzed the findings of teachers and students on the feasibility of robotic simulation through the project work as a teaching strategy and especially the improvement of indicators of the following basic skills: language, learning to learn, information processing and digital competence knowledge and interaction with the physical world. The results show a high appreciation of students and teachers about the project and its functionality in the cross and interdisciplinary development of key competencies.